Political Theology of Abolitionism: Beyond the Death Penalty - Lloyd, Vincent (Political theology, 2018)
Abolitionist has caught on, in the United States, as an identity for leftist political activists. Today's abolitionists grow out of a movement to oppose mass incarceration that itself is related to an earlier movement to oppose the death penalty, but in its current usage abolitionist suggests an opposition to multiple, interlinked systems of oppression. Jacques Derrida argues that death penalty abolitionists are best understood as opposing, and constituted by, political theology. Does the same apply when abolitionism is understood more broadly, as it is today? This paper explicates the meaning of abolitionist in left political circles today, summarizes Derrida's argument about the political theology of abolitionism, and concludes that some, but not all, aspects of Derrida's argument are applicable to today's abolitionists.